2001
DOI: 10.1161/01.hyp.37.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Central Antihypertensive Drugs

Abstract: Abstract-NO is known to be involved in the peripheral and central regulation of the cardiovascular function. It plays a neuromodulatory role via a direct action on presynaptic nerve terminals, stimulating the release of ␥-aminobutyric acid, glutamate, and norepinephrine. Our aim was to study the possible role of NO in the cardiovascular effects of the central antihypertensive drugs clonidine, rilmenidine, and ␣-methyl-norepinephrine (␣-MNA). Sites and mechanisms of the hypotensive action of these drugs were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Dobrucki et al (2001) showed that the a 2 -adrenoceptor/imidazoline receptor agonist clonidine, injected into the rat LV, decreased MAP and HR and simultaneously increased NO release in the NTS, and that blockade of NOS activity by injection of the NOS inhibitor N G -nitro-L-arginine-methyl ester (L-NAME) into the LV abolished these effects of clonidine. In contrast, intracisternal pretreatment with L-NAME in rabbits reduced the hypotension produced by an injection of a-methyl-noradrenaline (a 2 -adrenoceptor agonist), but not that induced by either clonidine or rilmenidine injected at the same site (Sy et al, 2001). Also in rabbits, blockade of NOS in the RVLM abolished the hypotension produced by central activation of a 2 -adrenoceptors, but not that induced by central activation of imidazoline receptors (Sy et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Dobrucki et al (2001) showed that the a 2 -adrenoceptor/imidazoline receptor agonist clonidine, injected into the rat LV, decreased MAP and HR and simultaneously increased NO release in the NTS, and that blockade of NOS activity by injection of the NOS inhibitor N G -nitro-L-arginine-methyl ester (L-NAME) into the LV abolished these effects of clonidine. In contrast, intracisternal pretreatment with L-NAME in rabbits reduced the hypotension produced by an injection of a-methyl-noradrenaline (a 2 -adrenoceptor agonist), but not that induced by either clonidine or rilmenidine injected at the same site (Sy et al, 2001). Also in rabbits, blockade of NOS in the RVLM abolished the hypotension produced by central activation of a 2 -adrenoceptors, but not that induced by central activation of imidazoline receptors (Sy et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…Nitric oxide (NO) is an important mediator that modulates cardiovascular function by a peripheral or central mechanism of action (Gardiner et al, 1990;Zanzinger et al, 1995;Colombari et al, 1998;Kadekaro & Summy-Long, 2000;Patel et al, 2001;Sy et al, 2001). The presence of the enzyme nitric oxide synthase (NOS) that catalyzes the synthesis of NO from L-arginine has been demonstrated in different areas of the central nervous system involved in cardiovascular control; these include the nucleus tractus solitarii (NTS), rostral ventrolateral medulla (RVLM), caudal ventrolateral medulla (CVLM) and paraventricular nucleus of the hypothalamus (PVN) (Vincent & Kimura, 1992;Patel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations